Classificação de ratings, sustentabilidade e previsão de default uma abordagem utilizando a regressão quantílica - Alves Filho, Cy Dy Augusto (2014)
The literature on analytical methods of accounting and corporate financial analysis models and cr edit indicators is large , and among the methods of credit risk classification is the classification model ratings, through which institutions classifie s customers according to their risk. However, the classical models of modeling credit risk using statisti cal techniques widely disseminated, as is the case of simple linear regression, the least squares method, among others. The quantile regression, evaluated in disseminated by Koenker and Basset (1978) has it as a main characteristic , analyzing the sample by the median and allow the analysis of subpopulations through the quantiles of the sample, which allows more specific inferences in according to the needs of the study. In recent years the concern with social and environmental issues have become increasing present in both the practical means and academia and in society in general, which brings up the idea of including the analysis of social indicators in environmental analysis credit, as already proposed in previous studies. However, the combined use of ec onomic, financial, social and environmental indicators, together with quantile regression, is an innovative proposal, and the subject of this academic study. This work is an exploratory and descriptive study , objective verify the possible contribution of t he inclusion of social and environmental variables, combined with the use of quantile regression for ratings classification and hence prediction of default. To fulfill this goal, we devel oped a database on panel, with the total of 561 observations, consist ing of data from publicly traded, its ratings, economic indicators, financial, social and environmental, the years 2007 to 2012 companies. With use of quantile regression was possible to infer that the social environmental variables are relevant for classi fication ratings and, consequently, to predict default.